GAMBARAN PERILAKU PENCEGAHAN PENULARAN TUBERKULOSIS DI SATU RUKUN TETANGGA INDONESIA BAGIAN BARAT - Meo, Julia Margareth; Sutrawiarsih, Kadek Alfin; Hia, Lili Selvia Agustina; Gultom, Eva Chris Veronica; Octaria, Martha (Universitas Sam Ratulangi, 2024)
Introduction : Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. tuberculosis bacteria can be spread through the air when a person with tuberculosis coughs, sneezes or talks and can be transmitted to other people directly or indirectly. Prevention of tuberculosis consists of implementing cough and sneeze etiquette behavior, wearing a mask, disposing of sputum in a special place, separating personal equipment from people with tuberculosis, maintaining the cleanliness of the home and surrounding environment, eating nutritious food, eating a healthy diet, maintaining proper housing density, seek treatment when symptomatic, wash hands and do not smoke. Objective: This study aims to determine the behavior of the community in an effort to prevent the transmission of tuberculosis in a neighborhood of Curug Kulon village, namely RT 001 / RW 07 Candu village. Methods: This type of research uses a descriptive quantitative design with a cross sectional approach. The number of samples in this study the instrument used was a questionnaire consisting of 14 questions. Data analysis using Microsoft Excel. The research was conducted in March 2024. Result: The results stated that the behavior of preventing Tuberculosis transmission in residents of RT 001 / RW 07 Curug Kulon village 55.22% had good behavior, 44.03% had sufficient behavior and 0.75% had poor behavior. Conclusion: The research results show that the majority of residents' behavior towards preventing tuberculosis transmission is in the good category. Therefore, Curug Kulon residents are expected to always implement behavior to prevent the transmission of tuberculosis. Keywords: Mycobacterium Tuberculosis;Prevention;Behaviour